Spontaneous Hemoperitoneum from a Ruptured Superficial Uterine Vessel in Third Trimester of Pregnancy - Nahar, Khairun; Begum, Hamida; Khatun, Mahmuda (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Spontaneous hemoperitoneum in third trimester of pregnancy is a very rare but lethal condition which demands prompt diagnosis and management for the survival of both mother and fetus. A 30 years old multipara woman presented at 34 weeks of pregnancy with acute abdominal pain and hypovolemic shock. Emergency exploratory laparotomy was done; an asphyxiated baby was born by cesarean section. One of multiple engorged superficial vessels on posterior surface of the uterus was found bleeding actively, which was then sutured. Post operative recovery of the patient was good. doi: 10.3329/bjog.v23i1.3055 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 32-34